Colombia : Improving Property Catastrophe Insurance Coverage of Public Infrastructure under Concessions - World Bank (Washington, DC, 2015)
The World Bank has been assisting the Government of Colombia (GoC) since 2012 in the preparation and implementation of an Integrated Disaster Risk Financing and Insurance (DRFI) strategy. To reduce GoC’s contingent liabilities to catastrophe risk, one component of the DRFI strategy seeks to enhance insurance requirements for concessions under Public Private Partnerships (PPPs). The World Bank delivered technical guidelines on insurance requirements for PPPs to the Ministry of Finance (MHCP). These have been integrated into the Master Insurance Contract, to which all PPPs must abide. The enhanced insurance contract provides minimum requirements for contract participants; standards and covers; underwriting information; and terms and conditions to reflect international (re)insurance market best practice.